Assessment of the effects of NPK fertilizer on edible yield and agro-biological parameters in a cowpea–amaranth intercrop - Mndzebele, Buhlebelive; Ncube, Bhekumthetho; Fessehazion, Melake; Mabhaudhi, Tafadzwanashe; Modi, Albert Thembinkosi (Frontiers in Sustainable Food Systems, 2023)
Estimates indicate that food and nutritional demand in Sub Saharan African nutrient-poor soils will exceed the high population demand. Vegetables such as amaranth and cowpea are key in contributing to food and nutritional security. Fertilisers are used to mitigate low nutrient levels in soils. The study aimed to investigate the effect of fertiliser application and intercropping on the yield and yield parameters of cowpea-amaranth vegetables. The experiment was laid out in a 2 x 4 factorial treatment structure in a completely randomized design, with intercropping and fertiliser as treatment factors with four replications. Biomass of amaranth and cowpea increased with addition of fertiliser application up to 100% NPK fertiliser level. Land utilisation showed values greater than one. Crop comparison showed that cowpea was more aggressive, had high actual yield loss and highly competitive compared to amaranth. More income could be obtained in intercropping. The research shows the benefit of fertiliser application in improving the biomass of amaranth and cowpea. Overall, the application of NPK fertilizer to amounts of up to 100%, based on the results of this study, resulted to higher biomass accumulation and improved intercropping indices.